The Stories Of Jesus' Birth A Critical Introduction - Freed, Edwin D. (London T&T Clark International, 2001)
This series is designed with the needs of introductory level students in mind. It should also appeal to general readers who want to be better informed about the latest advances in our understanding of the Bible and of the intellectual, political and relig
Keywords: Jesus Christ -- Nativity. Bible. -- Matthew, I-II -- Criticism, interpretation, etc. Bible. -- Luke, I-II -- Criticism, interpretation, etc. Infancy narratives (Gospels) Jesus Christ. Nativity of Jesus Christ